Romanian Theorists of Central European Integration - Nastasă-Kovacs, Lucian (Great Theorists of Central European Integration, 2023)
In the following chapter, we examine the map of intellectuals who attempted to solve the issues faced by their society by creating a theoretical framework for the political transformation of their country and region. By the second half on the 19th century, it had become clear that the Empire needed political and administrative reforms as well as a new approach toward the representation of minorities and different regions. Many young Transylvanian people undertook legal studies after 1849 as a reaction to the increasingly liberal attitudes of the provincial elite. In fact, among the most sought-after professions in the era were those of lawyers and notaries, a clear indication of a modernising society. In addition, attending an ‘academy’ or a law school constituted a somewhat convenient path that did not require a specific intellectual vocation but necessitated a university degree, which brought with it a social status and opened prospects for advancement. Moreover, these graduates were increasingly in demand to defend new types of interests, from the legal and economic affairs of various state or private institutions to those of individuals. Alexandru Petrino, Aurel C. Popovici, Ion Maiorescu, Constantin Isopescu-Grecul, and Nicolae Densusianu became pivotal figures in the debate and intellectual efforts related to the issue of federalisation or the reorganisation of the Empire and the distribution of political power based on a more equal principle. This fight was one of the most important movements of Romanian intellectuals and political leaders at the end of the 19th century and the first decade of the 20th century.KEYWORDS: reform, federalisation, Habsburg Empire, Austro-Hungary, rights, Maioresu, Popovici, Isopescu-Grecul, Densusianu, Petrino.